PENGEMBANGAN KURSUS ONLINE INTERAKTIF DENGAN SISTEM E-LEARNING DAN GAMIFIKASI - Dwi Susanto; Aliv Faizal Muhammad; Halimatus Sa'dyah; Salim Nabhan; Irwan Sumarsono (Universitas Negeri Medan, 2022)
Abstrak: Sejak wabah pandemi Cover-19, permintaan untuk menyediakan sumber daya pendidikan untuk pembelajaran jarak jauh terus meningkat. Karena keterlibatan belajar dan partisipasi aktif siswa menjadi beberapa aspek mendasar dari proses pembelajaran online mandiri yang efektif, aspek interaktivitas dan motivasi menjadi penting. Gamifikasi disarankan untuk diterapkan dalam pembelajaran online asinkron. Poin, penghargaan, catatan prestasi, dan aspek gamifikasi lainnya telah dilaporkan efektif dalam meningkatkan keterlibatan siswa dalam pembelajaran. Kelas bahasa Inggris akan menjadi contoh konten pembelajaran di sistem E-learning yang didukung gamification ini. Pembelajaran online ini dilengkapi dengan berbagai kuis yaitu pilihan ganda, drag and drop, isian, teka-teki silang, serta kuis dikte berbasis pengenalan suara. Aktivitas siswa dicatat sebagai poin. Hasil implementasi ini menunjukkan bahwa model tersebut dapat diterapkan untuk mata pelajaran lain untuk dikonversi atau disediakan dalam pembelajaran online, khususnya untuk gaya belajar mandiri melalui model e-learning asinkron.Keyword: Pembelajaran Bahasa Inggris, Wordpress, H5P, Gamifikasi, E-Learning Abstract: Since the Cover-19 pandemic outbreak, the demand for providing educational resources to distance learning keeps increasing. As students' learning engagement and active participation become some of fundamental aspects of effective autonomous online learning process, interactivity and motivational aspects become of necessity. Gamification is suggested to be implemented in an asynchronous online course. Points, rewards, and achievement records, and other gamification aspects have been reported effective in increasing students' engagement in the learning. An English course was to be the sample course content made available in an online course in which this gamification-supported E-learning system is implemented. The online course comes with types of quizzes namely multiple choice, drag and drop, fill in the blank, crossword puzzle, as well as speech recognition based dictation quiz. The students' activities are recorded as points awarded to the students' user page. The result of this implementation shows that the model can be implemented for other learning subject to be converted or made available in an online learning course, especially for autonomous learning style through asynchronous e-learning model.Keywords: Teaching English, Wordpress, H5P, Gamification, E-Learning